A Case for Description - Holmes, Carolyn E.; Guliford, Meg K.; Mendoza-Davé, Mary Anne S.; Jurkovich, Michelle (PS, political science & politics, 2024)
Descriptive research—work aimed at answering “who,” “what,” “when,” “where,” and “how” questions—is vital at every stage of social scientific inquiry. The creative and analytic process of description—through concepts, measures, or cases, whether in numeric or narrative form—is crucial for conducting research aimed at understanding politics in action. Yet, our field tends to devalue such work as “merely descriptive” (Gerring 2012), subsidiary to or less valuable than hypothesis-drive causal inference. This article posits four key areas in which description contributes to political science: in conceptualization, in policy relevance, in the management and leveraging of data, and in challenging entrenched biases and diversifying our field.